Reconnection rates and X line motion at the magnetopause: Global 2D‐3V hybrid‐Vlasov simulation results. Issue 3 (3rd March 2017) - Hoilijoki, Sanni; Ganse, Urs; Pfau‐Kempf, Yann; Cassak, Paul A.; Walsh, Brian M.; Hietala, Heli; von Alfthan, Sebastian; Palmroth, Minna
Abstract: We present results from a first study of the local reconnection rate and reconnection site motion in a 2D‐3V global magnetospheric self‐consistent hybrid‐Vlasov simulation with due southward interplanetary magnetic field. We observe magnetic reconnection at multiple locations at the dayside magnetopause and the existence of magnetic islands, which are the 2‐D representations of flux transfer events. The reconnection locations (the X lines) propagate over significant distances along the magnetopause, and reconnection does not reach a steady state. We calculate the reconnection rate at the location of the X lines and find a good correlation with an analytical model of local 2‐D asymmetric reconnection. We find that despite the solar wind conditions being constant, the reconnection rate and location of the X lines are highly variable. These variations are caused by magnetosheath fluctuations, the effects of neighboring X lines, and the motion of passing magnetic islands. Key Points: We study dayside magnetic reconnection in a global magnetospheric self‐consistent hybrid‐Vlasov simulation Flux transfer events are always present and the dayside X lines are influenced both by magnetosheath properties and other reconnection sites The local reconnection rate correlates well with an analytic prediction